Analysis of PAI Students' Experience in Participating in Campus Organizations and Its Impact on Personal Development - Saputri, Intan Dian; Shobahiya, Mahasri (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
This study aims to find out in depth the experiences of Islamic Religious Education (PAI) students in participating in campus organizations and their impact on self-development from academic, social, leadership, and religiosity aspects. This study uses a qualitative approach with a phenomenological method to explore the meaning of students' experiences directly. Data were obtained through in-depth interviews, field observations, and documentation of PAI students at Muhammadiyah University of Surakarta who are active in various types of campus organizations, both intra and extra. The data analysis technique refers to the Miles and Huberman model which includes three stages, namely data reduction, data presentation, and drawing conclusions. Data validity testing was carried out using triangulation techniques, both source and technique triangulation, to ensure the validity and reliability of the research findings. The results of the study showed that students' motivations for joining organizations included developing leadership skills, expanding social networks, gaining teamwork experience, and strengthening understanding and practice of Islamic teachings. Participation in organizations contributes to improving communication skills, time management, responsibility, decision making, and strengthening Islamic values ​​such as trustworthiness, honesty, cooperation, and discipline. The main challenges faced by students include difficulty in managing time, academic pressure, fatigue, and maintaining consistency of religious values ​​amidst organizational activities. Strategies used to overcome this include creating a regular schedule, setting priorities, and strengthening religious intentions and motivations. In conclusion, campus organizations contribute significantly to the holistic development of PAI students, as long as they are balanced with time management, spiritual awareness, and strong personal commitment in carrying out organizational activities consistently and responsibly.